2014
DOI: 10.2478/s11535-014-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α is associated with C2C12 Myoblast differentiation

Abstract: PGC-1α has been implicated as an important mediator of functional capacity of skeletal muscle. However, the role of PGC-1α in myoblast differentiation remains unexplored. In the present study, we observed a significant up-regulation of PGC-1α expression during the differentiation of murine C2C12 myoblast. To understand the biological significance of PGC-1α up-regulation in myoblast differentiation, C2C12 cells were transfected with murine PGC-1α cDNA and siRNA targeting PGC-1α, respectively. PGC-1α over-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…While the decreased constitutive expression of PGC-1α via transfection of shRNA-targeting PGC-1α leaded to no obvious myotube formation. The observation was parallel with our previous report that PGC-1α promoted typical myotube formation in murine C2C12 myoblast (Lin et al, 2014). These results suggested that PGC-1α was associated with myoblast differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…While the decreased constitutive expression of PGC-1α via transfection of shRNA-targeting PGC-1α leaded to no obvious myotube formation. The observation was parallel with our previous report that PGC-1α promoted typical myotube formation in murine C2C12 myoblast (Lin et al, 2014). These results suggested that PGC-1α was associated with myoblast differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…MRF4 is part of the myogenic regulatory factor family that drive muscle gene expression during myogenesis (Singh and Dilworth 2013) and the level of muscle MRF4 mRNA can increase as a response to both resistance and endurance exercise in untrained (Psilander et al 2003) and trained subjects (Yang et al 2005;Harber et al 2009). The present finding that only combined speed endurance and endurance exercise induced increased muscle MRF4 mRNA level may be caused by the upregulation of muscle PGC-1a mRNA, as PGC-1a has been shown to be associated with accelerated myoblast differentiation (Lin et al 2014 mitochondrial biogenesis, the crosstalk between PGC-1a and myoblast differentiation, may coordinate mitochondrial regulation. However, the observation that no change occurred in muscle MRF4 mRNA although the PGC-1a mRNA level increased with single-mode speed endurance exercise does not support this, and studies are needed to explore this possible relationship.…”
Section: Discussionmentioning
confidence: 47%
“…The present finding that only combined speed endurance and endurance exercise induced increased muscle MRF4 mRNA level may be caused by the upregulation of muscle PGC‐1 α mRNA, as PGC‐1 α has been shown to be associated with accelerated myoblast differentiation (Lin et al. ). Thus, it could be speculated that because PGC‐1 α is a master regulator of mitochondrial biogenesis, the crosstalk between PGC‐1 α and myoblast differentiation, may coordinate mitochondrial regulation.…”
Section: Discussionmentioning
confidence: 55%
“…Recent results point to a central role for the PGC-1␣ in integrating mitochondrial biogenesis and energy production with many diverse cellular functions. One laboratory has reported that the levels of PGC-1␣ mRNA were decreased in myogenic differentiation [21]. Another report proved NPY compromised the effect of db-cAMP on stimulating mRNA expression of PGC-1␣ in brown-like adipocytes [34].…”
Section: Discussionmentioning
confidence: 99%